2018
DOI: 10.3847/1538-4357/aabd38
|View full text |Cite
|
Sign up to set email alerts
|

On the Lack of Circumbinary Planets Orbiting Isolated Binary Stars

Abstract: We outline a mechanism that explains the observed lack of circumbinary planets (CBPs) via coupled stellar-tidal evolution of isolated binary stars. Tidal forces between low-mass, short-period binary stars on the pre-main sequence slow the stellar rotations, transferring rotational angular momentum to the orbit as the stars approach the tidally locked state. This transfer increases the binary orbital period, expanding the region of dynamical instability around the binary, and destabilizing CBPs that tend to pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 108 publications
0
63
0
Order By: Relevance
“…Indeed the two CB disks in our sample around P < 7 day binaries, V4046 Sgr and CoRoT 2239, have small mutual inclinations and do not host tertiaries capable of driving significant Lidov-Kozai oscillations (V4046 Sgr hosts a companion orbiting ∼12,000 au outside the disk; Kastner et al 2011). Two promising alternative explanations for the shortfall of CB planets around the shortest-period binaries are 1) a primordial phase of binary orbit expansion driven by pre-main-sequence tidal evolution which destabilizes planetary orbits (Fleming et al 2018) and 2) increased X-ray and EUV flux from tight, tidally locked binaries photoevaporates circumbinary planets to smaller planet radii (Sanz-Forcada et al 2014), which would remain undetected in the Kepler light curves.…”
Section: Circumbinary Planetsmentioning
confidence: 92%
“…Indeed the two CB disks in our sample around P < 7 day binaries, V4046 Sgr and CoRoT 2239, have small mutual inclinations and do not host tertiaries capable of driving significant Lidov-Kozai oscillations (V4046 Sgr hosts a companion orbiting ∼12,000 au outside the disk; Kastner et al 2011). Two promising alternative explanations for the shortfall of CB planets around the shortest-period binaries are 1) a primordial phase of binary orbit expansion driven by pre-main-sequence tidal evolution which destabilizes planetary orbits (Fleming et al 2018) and 2) increased X-ray and EUV flux from tight, tidally locked binaries photoevaporates circumbinary planets to smaller planet radii (Sanz-Forcada et al 2014), which would remain undetected in the Kepler light curves.…”
Section: Circumbinary Planetsmentioning
confidence: 92%
“…In the latter two systems, the CBP semimajor axis is relatively large (more than several times the critical separation for dynamical stability, see, e.g., fig. 1 of Fleming et al 2018), such that the effect of the 1:1 MMC is expected to be weak, and should not set the stability boundary. This is supported by a comparison of the maps for Kepler 47c and 1647 in Figs 3 and 4, which reveals that the stability regions for these systems are virtually identical for the single and binary star cases.…”
Section: Mean Motion Commensurabilitiesmentioning
confidence: 99%
“…These systems have revealed important clues for the formation and evolution of planets and high-order multiple systems. For example, none of the Kepler CBPs are orbiting binaries with periods shorter than 7 d, which suggests the presence of a third star Hamers et al 2016), or could be indicative of coupled stellar-tidal evolution (Fleming et al 2018). around the CBPs, Dvorak 1984).…”
Section: Introductionmentioning
confidence: 99%
“…While this dynamical feature of CBPs is well known (e.g., Dole 1964;Kane & Hinkel 2013;Forgan 2016;Popp & Eggl 2017), past works have not considered how the long-term tidal evolution of the host binary stars can impact the orbital evolution and habitability of CBPs. In this paper, we perform simulations of a single planet orbiting two stars with a binary orbital period (P orb ) less than ∼10 days, that is, where tidal forces are expected to strongly impact the binary orbit (Zahn & Bouchet 1989;Meibom & Mathieu 2005;Fleming et al 2018). We examine the orbital stability and long-term orbital oscillations of potentially habitable CBPs to determine the conditions that permit binary stars to host habitable CBPs, as well as to predict the properties and evolutionary histories of potentially habitable planets in those systems.…”
Section: Introductionmentioning
confidence: 99%
“…The coupled stellar-tidal evolution of binaries is complicated and can generate additional observable features beyond the circular orbits of short-period binaries. Fleming et al (2018) showed that for binary orbits with initial orbital periods less than about 8-10 days, the binary orbit will expand and become more eccentric as tidal torques transfer stellar rotational angular momentum into the binary orbit as the stars, in turn, contract along the pre-main sequence and tides drive the binary toward the tidally locked state. Following the earlier work of Verbunt & Zwaan (1981), Fleming et al (2018) showed that the binary orbit eventually decays due to the removal of angular momentum via magnetic braking after the stars' rotational frequencies are synchronized to the orbital frequency.…”
Section: Introductionmentioning
confidence: 99%